+0  
 
0
548
1
avatar+589 

What is the equation of this circle in general form?

x2+y2−2x−6y−26=0

x2+y2+2x+6y−26=0

x² + y² + 2x + 6y + 4 = 0

x2+y2−2x−6y+4=0

 

 

jbouyer  May 16, 2017
 #1
avatar+90058 
+2

 

The center is  (1,3)   and the radius  is 6  .....  so we have....

 

(x - 1)^2  + ( y - 3)^2  = 36        expand

 

x^2 - 2x + 1 + y^2 - 6y + 9  =  36     rearrange

 

x^2 + y^2 -2x - 6y  + 10  =  36      subtract 36 from both sides

 

x^2 + y^2  - 2x  - 6y - 26  =  0

 

 

cool cool cool

CPhill  May 16, 2017

44 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.